Pelatihan Dasar Jurnalistik Sebagai Citizen Journalist Bagi Remaja Asuhan Ar Ridho - Meliala, Robbikal Muntaha; Syahril, Romi; Shinta, Marlina Rahmi (Jurnal SOLMA, 2019)
Abstract This community empowerment had been conducted as one of facilitator to educate society especially the teenager who active in their social media, in order to be wise and good citizen journalist. The citizen journalist who active to contribute in national development by distributing news or articles which inline to journalistic ethic and science and not to be hoax news distributor. The benefit of this training is to empower teenager skill in writing and reporting a good news in right way so that they will be able to be a professional journalist in the future. Target of this training is teenager in age of 11 until 22 years old who active communicate and write through social media then have high curiosity toward social around. This training also had been expected as useful activity to build teenager talent in writing and profitable on social media. Keywords: Journalistic, Citizen Journalist, Teenager